THE RELATIONSHIP BETWEEN INTERIOR DESIGN AND ARCHITECTURE - Idaura Fadhya Che Ibrahim; Syed Ahmad Iskandar Syed Ariffin; Alice Sabrina Ismail (Journal of Islamic, Social, Economics and Development, 2022)
Architecture and interior design have struggled with how and where they intersect as professions and as academic disciplines. Architects believe that the design of interior space falls under their jurisdiction; that the architect is qualified by education and experience to design the interior and that they have always had this responsibility. At this time, the information stipulated on the knowledge areas and a set of skills published in the Interior Design Body of Knowledge is insufficient in providing clear guidance on the territories between interior design and architecture. There is a discrepancy in the information understood by the perspectives of education and industry in the definition of the profession. The need for clarity on what differentiates these two professions is a critical issue to avoid confusion and misrepresentation in professional roles and academic curricula structures. Henceforth, this study attempts to discuss the determinants shared similarly between architecture and interior design profession. The qualitative method is employed through a comparative and content analysis. Published and unpublished documents was retrieved from main databases which were Scopus, Science Direct, Google Scholars, Google engine search and the key professional associations, to facilitate the comparison. Reviewing the documents reveals that each profession acquires different knowledge. The findings showed that interior designers are not architects and not taught, qualified, or checked as architects. Conversely, architects are not educated, trained, or tested to be interior designers. The professions, on the other side, are complementary.